The importance of quantitative EGG for patients in a vegetative state in benzodiazepine test interpretation - L. N. Nerobkova; Yu. B. Filatova; A. L. Pylev; O. Yu. Kats (LLC "Publisher OKI", 2017)
Using the multiparameter method of EEG analysis with a complex study of coherent interband links with topographic mapping and localization of equivalent dipole sources of individual EEG components, characteristic signs of changes in intercentral neuronal connections at different stages of a vegetative state were obtained, features of structural and functional interrelations for patients in a vegetative state in benzodiazepine test interpretation of which identification can represent and interest for the output prediction and selection of adequate therapy.